2010
DOI: 10.1359/jbmr.091114
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A regulates monocyte migration through Rho small GTPases during osteoclastogenesis

Abstract: Osteoclastogenesis (OCG) results from the fusion of monocytes after stimulation with macrophage colony-stimulating factor (M-CSF) and receptor activator of NF-kB ligand (RANKL). Migration of monocytes into close proximity precedes critical fusion events that are required for osteoclast formation. Cellular migration requires leading-edge actin cytoskeleton assembly that drives cellular locomotion. Filamin A (FLNa) cross-links F-actin filaments in the leading edge of migrating cells and also has been shown to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 51 publications
(146 reference statements)
4
66
0
Order By: Relevance
“…The fusion first occurs to a portion of the filopodia. Previous reports have shown that FLNA, Rac1, and Rac2 are related to the OC chemotaxis during differentiation (Wang et al, 2008;Leung et al, 2010;Itokowa et al, 2011;Sun et al, 2013). FLNA allows Rho GTPases to accumulate at the front of filopodia, and a cascade amplifies the effect to Rho GTPases (Nobes and Hall, 1995;Ohta et al, 2006;Leung et al, 2010).…”
Section: Oc Fusion Processmentioning
confidence: 98%
See 4 more Smart Citations
“…The fusion first occurs to a portion of the filopodia. Previous reports have shown that FLNA, Rac1, and Rac2 are related to the OC chemotaxis during differentiation (Wang et al, 2008;Leung et al, 2010;Itokowa et al, 2011;Sun et al, 2013). FLNA allows Rho GTPases to accumulate at the front of filopodia, and a cascade amplifies the effect to Rho GTPases (Nobes and Hall, 1995;Ohta et al, 2006;Leung et al, 2010).…”
Section: Oc Fusion Processmentioning
confidence: 98%
“…FLNA is an actin-bound protein that forms a larger network with F-actin through cross-linking interactions (Stossel et al, 2001;Popowicz et al, 2006;Leung et al, 2010). The Rho GTPases are largely concentrated in the filopodia and function in cascade amplification by FLNA (Leung et al, 2010).…”
Section: Oc Differentiation and Expression Of Specific Enzymesmentioning
confidence: 99%
See 3 more Smart Citations